PERLINDUNGAN HAK DESAIN INDUSTRI PADA KEMASAN CUSHION: ANALISIS KOMPARATIF CUSHION TRUE TO SKIN DAN GLAD2GLOW - Wahyu Suwarni (P3M Politeknik Negeri Media Kreatif, 2025)
Packaging design plays a crucial role in product differentiation and brand identity formation, especially in the highly competitive cosmetics industry. This research aims to analyze the potential plagiarism of packaging designs for cushion products from the brands True To Skin and Glad2Glow, as well as their impact on the distinctiveness of each product. The research approach used is qualitative with a comparative method. Data was collected through literature study and in-depth visual analysis of the design elements of both products' packaging. The results of the study indicate a significant similarity in several aspects of the packaging design, which could potentially create confusion among consumers and threaten the uniqueness of each brand's visual identity. The implications of this research highlight the need for greater awareness regarding the importance of industrial design rights protection for industry players in the cosmetics sector. Registering packaging designs as intellectual property becomes a preventive measure.